A Laplace's principle based approach for solving fuzzy matrix games - Larbani, Moussa (NOVA Publisher, 2010)
We introduce a solution for matrix games with fuzzy payoffs via the α -cuts and the introduction of Nature as a third player expressing the uncertainty involved in the game. The beliefs of players about the behavior of Nature are based on the Laplace’s principle of “insufficient reason”. Moreover, we provide a procedure for computing the introduced solution.